Histomorphometric changes in the ovaries of thymectomized guinea pigs - Punniakotti, Murali; V.Nithya; James Villanueva (Italian Journal of Anatomy and Embryology, 2022)
Hypothalamic-pituitary-gonadal axis function is necessary for maintaining proper female reproductive cycle. This study aimed to evaluate the ovarian histomorphometric and histoarchitectural changes in neonatal, prepubertal and pubertal thymectomized female guinea pigs. A total of 30 female guinea pigs, sham-operated (n-5) and thymectomized (n-5) were studied in each group. The diameter and number of ovarian follicles among the thymectomized and sham operated female guinea pigs during estrus phase of estrous cycle was compared. Gonadal and accessory reproductive organs weights and microscopic features were studied in the sham operated guinea pigs and thymectomized. There were statistically significant changes in the number and diameter of follicles in the ovary in neonatal thymectomized female guinea pigs, but no significant changes were observed in prepubertal and pubertal female guinea pigs. Neonatal thymectomized female guinea pigs showed significant changes in their weight as well as changes in the microscopic features including reduced thickness of myometrium of uterus and less mucosal folding in the fallopian tube compared to the sham-operated group. But prepubertal and pubertal thymectomy did not affect the weight and microscopic features of gonads and accessory reproductive organs. Depending on the time of thymectomy, these results indicate morphological changes in the ovaries after thymectomy in females.